2017
DOI: 10.1111/nyas.13357
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, structure, and bioactivities of polysaccharides from Cyclocarya paliurus (Batal.) Iljinskaja

Abstract: Cyclocarya paliurus (Batal.) Iljinskaja, a well-known edible and medicinal plant, has been widely used in China as a traditional medicine for treating hypertension and diabetes. C. paliurus possesses various bioactivities, such as antihyperglycemic, antihyperlipidemic, antihypertensive, anticancer, antifatigue, antioxidation, antimicrobial, colon health-promoting, and immunological activities. Polysaccharides, as natural macromolecules with various biological activities, are considered to be the main effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Cyclocarya paliurus is a plant of the genus Chrysanthemum (Jugaceae), mainly distributed in southern China. Its branches and leaves are sweet, having a cooling effect, and can reduce swelling and pain [5]. Modern pharmacological studies have shown that Cyclocarya paliurus contains a variety of nutrients and can play different biological roles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclocarya paliurus is a plant of the genus Chrysanthemum (Jugaceae), mainly distributed in southern China. Its branches and leaves are sweet, having a cooling effect, and can reduce swelling and pain [5]. Modern pharmacological studies have shown that Cyclocarya paliurus contains a variety of nutrients and can play different biological roles [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the national key protected endangered plants in China [13]. It was found that CP contains a variety of biological active ingredients, such as polysaccharides, flavonoids, saponins, and triterpenes [35], and thus has the pharmacological effects of hypoglycemia [6], lowering blood pressure [7], and hypolipidemia [811]. In addition, previous studies showed that C. paliurus aqueous extract inhibited α-glucosidase activity and decreased blood glucose level in diabetic mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Iljinsk ( C. paliurus ), a plant of the genus Cyclocarya (Juglandaceae), is the sole species in its genus and is unique to China (8). It is mainly distributed in Southern China and grows at 420–2,500 m altitude in mountainous humid evergreen forests (8,9). Its branches and leaves taste sweet, have a cooling effect, and may reduce swelling and pain (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly distributed in Southern China and grows at 420–2,500 m altitude in mountainous humid evergreen forests (8,9). Its branches and leaves taste sweet, have a cooling effect, and may reduce swelling and pain (8). From its leaves, Chinese populations produce health tea, commonly termed ‘sweet tea’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation